Why do we work? / Azman Taher - Taher, Azman (Universiti Teknologi MARA, Pahang, 1988)
Why do we work? Why do we strive for excellence? How can managers influence subordinate in such a way to bring out the best in them? For what seemed to be quite a straight forward question, the answers may tum out to be very complex. Understanding these facts need full understanding of motivation that which causes, channels, and sustains people's behaviour. Managers today are utilizing the elements of motivation to lead and influence their subordinates effectively. Management, as defined by Mary Parker Follet, is the art of gertting work done through people.2 However, people are complex figures with unlimited wants. Therefore, the key to understanding motivation is to investigate, analyze and subsequently satisfy these needs and wants accordingly. However, the common situation faced· by subordinates is that, superiors see them as who they should be or supposed to be rather than who they really are. Individuals excel in different and sometimes in strange ways. We cannot and sometimes it is impossible to evaluate someone's effort and behaviour based on a general, ideal or rigid model. In evaluating subordinates too, we need to understand the concepts of motivation. Managers LOO, need to understand the reasons why do we work? A. F. Stoner and Charles Wankel in their book "Management", have classified the reasons we work and strive for excellence into three different models. These models are the Traditional, Human Relations and Human Resources Models. The mentioned models will be further elaborated in later parts of this paper. These models are not separate or extensions to Maslow's Hierarchy of Needs but as a matter of fact are condensations of the latter.